John Hope, the Foot-Ball Club of 1824 and its sporting legacy. (2nd January 2018) - Hutchinson, John; Mitchell, Andy
Abstract : The Foot-Ball Club which was formed in Edinburgh, Scotland's capital city, in 1824, is the world's first known organization dedicated to football. Founded by John Hope, then a student lawyer, it remained active until 1841, yet during its existence the club kept a low profile and not a single mention of its activities has been located in contemporary newspapers. This absence raises the pertinent question as to what other football activities may also have taken place in early nineteenth-century Britain, similarly unreported and therefore unknown. An examination of the Foot-Ball Club's activities is only possible due to Hope's obsession with recording and preserving the minutiae of his life, which extended to over 200 boxes of personal papers by his death. The authors have undertaken a detailed analysis of the club, revealing a web of influence far wider than was previously realized. Their paper expands upon already familiar material about John Hope's Foot-Ball Club, and details who the club members were, explaining how they interlinked through sport and work, how they impacted upon Edinburgh society and outlining their connections to the next generation of footballers. They conclude that this was not just a quirky, historically isolated football club for gentlemen in one particular city, but one which spawned a close-knit web of interests and relationships which had a significant influence on the early and long-term development of the game of football.